2013
DOI: 10.1007/978-1-4614-6217-0_12
|View full text |Cite
|
Sign up to set email alerts
|

Decisions on the Road to Memory

Abstract: A fundamental property of the adaptive immune system is the ability to generate antigen-specific memory, which protects against repeated infections with the same pathogens and determines the success of vaccination. Immune memory is built up alongside a response providing direct protection during the course of a primary immune response. For CD8 T cells, this involves the generation of two distinct types of effector cells. Short lived effector cells (SLECs) confer immediate protection, but contribute little to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…It will be important to determine whether certain effector T cells that modulate glycolysis and switch to OXPHOS, fatty acid oxidation (FAO), and/or autophagy can preferentially enter the memory pool in part by escaping RICD (5, 31, 36). Recently identified effector T cell subsets such as short-lived effectors (SLEC) and memory precursor (MPEC) T cells differ in their survival and potential for memory formation (37, 38), which may be influenced by a divergence in glycolysis-dependent RICD sensitivity. For example, exposure to cytokines like IL-15 might protect selected effectors from RICD by facilitating a switch from aerobic glycolysis to OXPHOS (4, 38-40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be important to determine whether certain effector T cells that modulate glycolysis and switch to OXPHOS, fatty acid oxidation (FAO), and/or autophagy can preferentially enter the memory pool in part by escaping RICD (5, 31, 36). Recently identified effector T cell subsets such as short-lived effectors (SLEC) and memory precursor (MPEC) T cells differ in their survival and potential for memory formation (37, 38), which may be influenced by a divergence in glycolysis-dependent RICD sensitivity. For example, exposure to cytokines like IL-15 might protect selected effectors from RICD by facilitating a switch from aerobic glycolysis to OXPHOS (4, 38-40).…”
Section: Discussionmentioning
confidence: 99%
“…Recently identified effector T cell subsets such as short-lived effectors (SLEC) and memory precursor (MPEC) T cells differ in their survival and potential for memory formation (37, 38), which may be influenced by a divergence in glycolysis-dependent RICD sensitivity. For example, exposure to cytokines like IL-15 might protect selected effectors from RICD by facilitating a switch from aerobic glycolysis to OXPHOS (4, 38-40). …”
Section: Discussionmentioning
confidence: 99%
“…However, there were also important differences in the responses generated by these different formulations. Although adjuvant-induced inflammation can sometimes promote short-rather than longterm immunity, 34,35 we found that the LD-AS03-adjuvanted formulations were the most effective at inducing long-term memory responses in our mouse model. These formulations elicited very different antigen-specific cytokine/chemokine profiles and patterns of antigen-specific CD4C T cells in re-stimulated splenocytes compared to the HD-unadjuvanted vaccine.…”
Section: Discussionmentioning
confidence: 65%
“…In the Asymmetrical Division hypothesis, the SLEC vs MPEC fate decision is made during the first cell division via asymmetrical partitioning of factors, such as atypical protein kinase C, mTOR, and c-myc (Arsenio, Metz, & Chang, 2015; Pollizzi et al, 2016; Verbist et al, 2016). Studies have shown that the daughter T cell proximal to the antigen-presenting cell has a greater propensity to differentiate into a SLEC, whereas the distal daughter T cell preferentially differentiates into a MPEC (Amsen, Backer, & Helbig, 2013; Gerritsen & Pandit, 2016). While this early partitioning of cellular factors likely plays a role, studies suggest that subsequent signals can influence T cell fate.…”
Section: Chemokines and Memory T Cell Development: Location Determinementioning
confidence: 99%